New Prospective for the Management of Low-Risk Pulmonary Embolism: Prognostic Assessment, Early Discharge, and Single-Drug Therapy with New Oral Anticoagulants - Alessandro Squizzato (Scientifica)
Patients with pulmonary embolism (PE) can be stratified into two different prognostic categories, based on the presence or absence of shock or sustained arterial hypotension. Some patients with normotensive PE have a low risk of early mortality, defined as <1% at 30 days or during hospital stay. In this paper, we will discuss the new prospective for the optimal management of low-risk PE: prognostic assessment, early discharge, and single-drug therapy with new oral anticoagulants. Several parameters have been proposed and investigated to identify low-risk PE: clinical prediction rules, imaging tests, and laboratory markers of right ventricular dysfunction or injury. Moreover, outpatient management has been suggested for low-risk PE: it may lead to a decrease in unnecessary hospitalizations, acquired infections, death, and costs and to an improvement in health-related quality of life. Finally, the main characteristics of new oral anticoagulant drugs and the most recent published data on phase III trials on PE suggest that the single-drug therapy is a possible suitable option. Oral administration, predictable anticoagulant responses, and few drug-drug interactions of direct thrombin and factor Xa inhibitors may further simplify PE home therapy avoiding administration of low-molecular-weight heparin.